The Impact of Alleged Israeli Genocide in Palestine: An Analytical Review - Ghanim ismail (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2024)
The Israeli-Palestinian conflict, a deeply rooted and prolonged struggle, has been the subject of extensive international debate and scrutiny. This article delves into the contentious allegations of genocide perpetrated by Israel against the Palestinian population. By examining the historical context, political dynamics, humanitarian impact, and international responses, this study seeks to provide a nuanced and comprehensive analysis of the situation. Beginning with a detailed overview of the term "genocide" as defined by the United Nations Genocide Convention of 1948, the article assesses whether the actions of Israel align with this legal definition. The historical context traces the conflict from the pre-1948 period, through the establishment of Israel and the subsequent wars, to the current state of affairs. The examination of political and social dynamics includes an analysis of Israeli policies towards Palestinians, the response and actions of Palestinian governance, and the role of media and propaganda in shaping public perception. This comprehensive review synthesizes the evidence and arguments from various perspectives, questioning the applicability of the term "genocide" and exploring alternative frameworks such as ethnic cleansing, apartheid, or crimes against humanity. The conclusion underscores the complexity of the conflict and the importance of continued dialogue, humanitarian efforts, and pursuit of a peaceful resolution. Through this analytical lens, the article aims to contribute to a deeper understanding of the Israeli-Palestinian conflict and the severe humanitarian issues at its core.